2012
DOI: 10.1039/c2nr31775c
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of mesoporous bioactive glass nanoparticles to deliver therapeutic molecules

Abstract: Inorganic bioactive nanomaterials are attractive for hard tissue regeneration, including nanocomponents for bone replacement composites and nanovehicles for delivering therapeutics. Bioactive glass nanoparticles (BGn) have recently gained potential usefulness as bone and tooth regeneratives. Here we demonstrate the capacity of the BGn with mesopores to load and deliver therapeutic molecules (drugs and particularly genes). Spherical BGn with sizes of 80-90 nm were produced to obtain 3-5 nm sized mesopores throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 68 publications
3
97
0
1
Order By: Relevance
“…The cytotoxicity of the inert mesoporous nanomaterials is generally influenced by numerous factors including particle size, pore size, and surface chemistry [60,71,72]. The cell viability of both MBG nanocarriers was observed to be dose-and time-dependent.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The cytotoxicity of the inert mesoporous nanomaterials is generally influenced by numerous factors including particle size, pore size, and surface chemistry [60,71,72]. The cell viability of both MBG nanocarriers was observed to be dose-and time-dependent.…”
Section: Discussionmentioning
confidence: 96%
“…The internal mesoporous characteristics of MBG are similar to those of other MSNs, but their major advantage is their bonebioactivity related to ionic release as well as their degradability [55][56][57][58]. In our recent studies, MBG have shown a high level of mesoporosity for loading and sustained release of biomolecules, including chemical drugs and genes [59][60][61]. In addition, MBG allowed intracellular uptake via endocytosis without cell or tissue damage [60].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…growth factors and anticancer drugs), owing to the small particle size, for specific intended purposes. 4,5 The incorporation of biomolecules in bioceramics or bioactive glasses (BG) can enhance the therapeutic effects of the materials in bone regeneration 6 or anticancer treatments. 5 However, the relatively short shelf-life, the sensitivity to outer conditions, and the high cost of most biomolecules (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The siRNA-nanoparticles were also easily taken up by the cells with a transfection efficiency of up to 80 %. It may be a promising drug release system in bone tissue regeneration [48].…”
Section: Inorganic Nanoparticle-based Systemmentioning
confidence: 99%